Critic Literature: Phenomenological Psychology (Phenomenology, Humanities and Sciences, 2023)
Vozes has just launched an important editorial project within the well-known Coleção Pensamento Humano: Phenomenological Psychology and Transcendental Phenomenology – Selected Texts (1927-1935). Authored by Edmund Husserl, this volume brings together, for the first time, in a vernacular version, capital manuscripts that, for a long time, remained unpublished by the German master; such works concerning the project of a phenomenologically oriented psychology under the backdrop of his propositional transcendental idealism. With the translation of Giovanni Jan Giubilato, Anna Luiza Coli, Daniel Guilhermino and Felipe Maia da Silva, the precious material added texts between 1927 and 1935. How then does this general state of the art come about?The volume contains, essentially, three parts arranged chronologically. The first is The Encyclopedia Britannica Article (1927). The second is The Amsterdam Conferences (1928). And the third, The Prague Conferences (1935).
Keywords: Husserl; Phenomenological Psychology; Critical Literature